Correction: Kirkegaard-Biosca et al. Cefiderocol for the Treatment of Infections by VIM-Type-Producing Gram-Negative Bacteria. Antibiotics 2024, 13, 874 - Cristina Kirkegaard-Biosca; Ester del Barrio-Tofiño; Miguel Villamarín; Nieves Larrosa; David Campany; Juan José González-López; Ricard Ferrer; Belén Viñado; Laura Doménech; Julia Sellarès-Nadal; Laura Escolà-Vergé; Nuria Fernández-Hidalgo; et al. (Antibiotics)
Error in Table 2 [...]